A 3D Silverton-Type Polyoxomolybdate Based on PrMo12O42: Synthesis, Structure, Photoluminescence and Magnetic Properties - Zhao, Yanxin; Sun, Xiaopeng; Ji, Yanfang; Kong, Hui; Chen, Shumin; Ma, Pengtao; Niu, Jingyang; Wang, Jingping (Frontiers in Chemistry, 2021)
A three-dimensional (3D) Silverton-type polyoxomolybdate (POMo) with the formula of NH4{Mn4[PrMo12O42]}·18H2O (1) was successfully isolated and well established by single crystal X-ray diffraction technique, X-ray powder diffraction pattern, infrared spectrum, thermogravimetric and elemental analyses. The inorganic building block PrMo12O42 was extended to a 3D framework via the MnO6 bridge. The excitation of solid-state sample of compound 1 at 375 nm displays red emission. Besides, variable temperature magnetic susceptibilities measurements indicate that the magnetic behavior in compound 1 is dominated by antiferromagnetic interactions.